The Viking's royal temptation - Harper, Roxy (Harlequin historicals., 2025)
"Princess and healer Theadora doesn't flinch at the sight of armed soldiers. Yet when another uprising threatens to disturb Constantinople's peace, and Varangian guard Erik bursts into her sanitorium, she's stunned by her body's immediate reaction to the rugged Viking. After the tragic loss of his family, Erik vowed to never love again. So he refuses to let his inconvenient attraction to Thea distract him from his duty: escorting her to marry the king of Macedonia. If Thea doesn't wed, her people will suffer, so can the star-crossed lovers fight their feelings, as well as their enemies?"--